MORPHO-SYNTAKTISCHE MERKMALE DER IRONIE ALS BEWEIS FÜR CROSSWRITING IN ERICH KÄSTNERS DER GESTIEFELTE KATER English Title: MORPHO-SYNTACTIC FEATURES OF IRONY AS PROOF OF CROSSWRITING IN ERICH KÄSTNER’S PUSS IN BOOTS - Liana-Mărioara Colban; Anita Andrea Széll (Journal of Languages for Specific Purposes, 2024)
Irony is a complex linguistic phenomenon that plays an important role in children’s literature. The use of irony in a children’s literary text opens up new possibilities for interpreting the text and also brings about an important change in the level of reception of the work, as it awakens not only the curiosity of the children but also the interest of the adults. The aim of this paper is to examine the forms of irony based on Erich Kästner’s fairy tale “Puss in Boots” and to discuss the role of morphology and syntax in generating irony. A detailed analysis of the morpho-syntactic elements of irony should show that Kästner’s text can be classified in the category of crosswriting. The paper also deals with the writing style of Kästner. Typical of the German author is that he has often made adaptations of famous works of children’s and young people’s literature. “Till Eulenspiegel”, “Münchhausen” and “Die Schildbürger” are adaptations that show that Kästner is interested in works that have the potential to be humorous. Earlier versions of the fairy tale “Puss in Boots” are also briefly mentioned in this paper to illustrate the popularity of the pre-text. Because Kästner’s text is an adaptation of the fairy tale of the Brothers Grimm, the following important terms are also to be explained: irony, humour and intertextuality. However, the article focuses mainly on the morpho-syntactic peculiarities of Kästner’s adaptation. Different grammatical categories such as modal particles, modal verbs, attributes and punctuation are examined in the paper and this analysis tries to determine to what extent they play a role in the manifestation of irony. Such an analysis opens up new perspectives and possibilities of interpretation of the fairy tale “Puss in Boots” by Kästner.